Eksplorasi Mikroflora Alami Produk Fermentasi Tradisional Cangkuak Berbasis Daging di Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - Adela Putri; Nurmiati Nurmiati; Periadnadi Periadnadi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Cangkuak is a fermented food made from meat with betung bamboo shoots or kluwak, salt and rice. The fermentation process is carried out without adding microbial cultures (spontaneous) for one to three weeks in a tightly closed container. cangkuak's manufacturing technique, ingredient formulation and constituent ingredients are unique, resulting in a final product with different characteristics. Research on the presence of microbes in fermented food products (fish, milk, vegetables) has been widely conducted, but information on exploring the presence of natural microflora and the in vitro potential of fermenting bacteria in cangkuak has never been reported. This research was conducted using a survey method and the resulting data were presented descriptively. It was found that the natural microflora found in the three samples of cangkuak in Kuantan Mudik was dominated by bacteria, with the highest proportion of bacterial groups in the three cangkuak samples being fermentative bacteria (2.0 - 6.30x105 cfu/g), cellulolytic bacteria (3.30 - 5.90x105 cfu/g), amylolytic bacteria (1.70 - 4.40x105 cfu/g), proteolytic bacteria (0.12 - 7.90x105 cfu/g), lipolytic bacteria (0.08 - 0.12x105 cfu/g). Six potential fermentative isolates were obtained as evidenced by the calculation of index values, namely DK-I1 (1.59), DR-I1 (1.36), DR-I2 (2.49), DR-I3 (1.19), DKR-I1 (2.41), and DKR-I2 (2.96).